Importance of asymptotic freedom for the pseudocritical temperature in magnetized quark matter - Farias, R. L.S.; Gomes, K. P.; Krein, G. [UNESP]; Pinto, M. B. (American Physical Society (APS), 2014)
Although asymptotic freedom is an essential feature of QCD, it is absent in effective chiral quark models like the Nambu-Jona-Lasinio and linear sigma models. In this work we advocate that asymptotic freedom plays a key role in the recently observed discrepancies between results of lattice QCD simulations and quark models regarding the behavior of the pseudocritical temperature Tpc for chiral-symmetry restoration in the presence of a magnetic field B. We show that the lattice predictions that Tpc decreases with B can be reproduced within the Nambu-Jona-Lasinio model if the coupling constant G of the model decreases with B and the temperature. Without aiming at numerical precision, we support our claim by considering a simple ansatz for G that mimics the asymptotic-freedom behavior of the QCD coupling constant 1/αs∼ln(eB/ΛQCD2) for large values of B. © 2014 American Physical Society.